1991
DOI: 10.1007/bf00925822
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a school-based cognitive-behavioral intervention for ADHD children

Abstract: Two variations of school-based cognitive-behavioral training (CBT) program were compared to each other and to a waiting-list control condition in the treatment of children with attention-deficit hyperactivity disorder (ADHD). The experimental interventions included a multicomponent condition that provided coordinated training programs for parents, teachers, and children and a teacher-only condition that offered training for classroom teachers only. Evaluation of outcome occurred at pre-intervention, post-inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 11 publications
0
59
0
Order By: Relevance
“…For the non-RCTs, the mean (SD) sample size was 38.1 (26.0) and comprised, on average, a mean (SD) of 23% (0.17) females. Some of the studies described participants as using medication for ADHD (n = 28: 19 RCTs;142,143,(159)(160)(161)(162)164,165,(167)(168)(169)172,173,177,178,180,182,183,186 9 non-RCTs 141,189,[192][193][194]197,[200][201][202] ) whereas some reported that no medication for ADHD was used (n = 11: 9 RCTs; 104,153,158,170,174,175,179,181,187 two non-RCTs 195,196 ). The reports for the remaining 15 studies did not clarify whether or not medication for ADHD was used (n = 15: 11 RCTs; [154][155][156][157]163,…”
Section: Study and Participant Information: Descriptive Statisticsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the non-RCTs, the mean (SD) sample size was 38.1 (26.0) and comprised, on average, a mean (SD) of 23% (0.17) females. Some of the studies described participants as using medication for ADHD (n = 28: 19 RCTs;142,143,(159)(160)(161)(162)164,165,(167)(168)(169)172,173,177,178,180,182,183,186 9 non-RCTs 141,189,[192][193][194]197,[200][201][202] ) whereas some reported that no medication for ADHD was used (n = 11: 9 RCTs; 104,153,158,170,174,175,179,181,187 two non-RCTs 195,196 ). The reports for the remaining 15 studies did not clarify whether or not medication for ADHD was used (n = 15: 11 RCTs; [154][155][156][157]163,…”
Section: Study and Participant Information: Descriptive Statisticsmentioning
confidence: 99%
“…Ten studies 155,153,163,169,178,184,186,192,198,202 were dissertations or theses (n = 10: 7 RCTs; 3 non-RCTs); the remaining were journal articles (n = 42: 104,[141][142][143]153,154,[157][158][159][160][161][162][164][165][166][167][168]170,[172][173][174][175][176][177][179][180][181][182][183]185,[187][188]190,191,[193][194][195][196][197][199]…”
Section: Study and Participant Information: Descriptive Statisticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, more recently developed "cognitive-behavioral" treatments (e.g. self-monitoring, verbal self-instruction, problem-solving training, self-reinforcement) have also failed to promote improvement in the primary symptoms of ADHD or significant changes in the behavior or academic functioning of children diagnosed with ADHD (Abikoff et al, 1988;Bloomquist, August, & Ostrander, 1991;Brown, Borden, Wynne, Spunt, & Clingerman, 1987; National Institute of Health [NIH], 1998). However, children and teens who are being subjected to parental neglect or abuse will often respond favorably to individual and family therapy (as well as community-based interventions from Child Protective Agencies) that address these issues.…”
Section: Adjunctive Treatmentsmentioning
confidence: 99%